Evaluasi Kualitas Internal dan Eksternal Telur Ayam Kampung yang Diawetkan dengan Daun Belimbing Wuluh (Averrhoa bilimbi L.) - Supranoto Supranoto; Fani Dwi Evadewi; Tri Sukmaningsih; Rosanti Rosanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Free-range chicken eggs are a source of high-value animal protein but are susceptible to quality deterioration during storage. This study aimed to evaluate the effect of Averrhoa bilimbi L. leaf extract concentration and storage duration on the internal quality (Egg White Index, Egg Yolk Index, Haugh Unit, yolk color) and pH of free-range chicken eggs. An experimental method was employed using a Completely Randomized Design (CRD) with a 4 x 4 factorial pattern. The first factor was leaf extract concentration (0%, 5%, 10%, 15%), and the second factor was storage duration (7, 14, 21, and 28 days). The results showed that immersion in 5% Averrhoa bilimbi L. leaf extract significantly maintained internal egg quality compared to the control up to 14 days of storage. This treatment produced optimal values for the Egg White Index, Egg Yolk Index, Haugh Unit, and yolk color score, while also inhibiting the pH increase indicative of egg spoilage. However, an excessively high concentration (15%) resulted in physical quality degradation. It is concluded that Averrhoa bilimbi L. leaf extract has potential as an effective natural preservative for maintaining the freshness of free-range chicken eggs, with the best concentration at 5% for short- to medium-term storage.